Co‐culture model reveals the characteristics of theca cells and the effect of granulosa cells on theca cells at different stages of follicular development. Issue 1 (9th November 2020) - Gan, Xiang; Wang, Yushi; Gao, Shanyan; Chen, Xi; Hu, Shenqiang; Wang, Jiwen; Hu, Jiwei; Li, Liang; Han, Chunchun
Abstract: Theca cells (TCs) play an important role in follicular development, which cannot be separated from granulosa cells (GCs). However, compared with mammals, the TCs and the effects of GCs on TCs at different follicular development stages (FDSs) have specific characteristics in avian species, but none of them have been clearly defined. In this study, we established an in vitro co‐culture (with GC at the corresponding stage) model of goose TCs at different FDSs (pre‐hierarchical, hierarchical and F1) by using a transwell system. The properties of TCs in co‐culture at the three FDSs, including cell morphology, activity and intracellular lipid content, as well as the expression of key genes involved in de novo lipogenesis, steroidogenesis, proliferation and apoptosis, were examined and defined. We further compared the mono‐culture and co‐culture groups. After co‐culture, the activity of TCs showed significant ( p < .01) increases in all stages; moreover, in pre‐hierarchical TCs, the expression levels of FAS, SREBP, 3β‐HSD and CCND1 were promoted, and PPARγ, CYP19, BCL2 and CAS3 were inhibited ( p < .05); in the hierarchical TCs, the expression levels of PPARγ, FAS, CYP19, CCND1 and BCL2 were promoted, and SREBP, STAR, 3β‐HSD and CAS3 were inhibited ( p < .05), whereas in the F1 TCs, the expression levels of PPARγ, FAS, 3β‐HSD, CYP19 and CCND1 were promoted, and STAR and CAS3 were inhibited ( p < .05). These results suggested that GCs at the three FDSs have dynamic and complex influences on the physiological characteristics of TCs, and the influences on TCs at the three FDSs were varied.